2017
DOI: 10.3390/ijerph14121480
|View full text |Cite
|
Sign up to set email alerts
|

Dental Procedures in Primary Health Care of the Brazilian National Health System

Abstract: The aim of this study was to examine the procedures of primary dental health care performed by oral health teams (OHTs) adhering to the second cycle of the ‘National Programme for Improving Access and Quality of Primary Care’ (PMAQ-AB) in Brazil. A cross-sectional descriptive analysis was performed, across 23 dental procedures comprising preventive, restorative/prosthetic, surgical, endodontic and oral cancer monitoring. Descriptive analysis shows that most of the oral health teams carry out basic dental proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 10 publications
3
23
0
4
Order By: Relevance
“…These OHTs also receives high incentives from the UHS, which could explain the results of this study [34]. Previous studies, using PMAQ-AB data, also found differences between Brazilian macro-regions when evaluating the relationship between primary and secondary care in public health services [35] and procedures of primary dental health care performed by the OHTs [36]. Both studies observed the best results for OHTs in the Southern and Southeastern regions, reinforcing the great social disparities between the Brazilian regions, even though the UHS does offer actions and services to promote, prevent, treat and improve the health of all Brazilians in all regions [37].…”
Section: Discussionmentioning
confidence: 55%
“…These OHTs also receives high incentives from the UHS, which could explain the results of this study [34]. Previous studies, using PMAQ-AB data, also found differences between Brazilian macro-regions when evaluating the relationship between primary and secondary care in public health services [35] and procedures of primary dental health care performed by the OHTs [36]. Both studies observed the best results for OHTs in the Southern and Southeastern regions, reinforcing the great social disparities between the Brazilian regions, even though the UHS does offer actions and services to promote, prevent, treat and improve the health of all Brazilians in all regions [37].…”
Section: Discussionmentioning
confidence: 55%
“…However, the increase in the frequency of reporting dental prosthesis procedures by OHT from Northeast region is a quite interesting and positive finding. Differences in the management of PHC services and difficulties in the access of people in deprived areas could explain these regional differences in Brazil (18). It is urgent to carried out more analytical studies to understand and surpass these inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…Provisional analysis of data obtained from the external evaluation phase of the first and second cycles of PMAQ-AB was conducted, showing that the majority of the dental teams executed preventive, restorative, endodontic and surgical dental procedures. However, concerning the procedures related to dental prostheses, although they identified people in the need, few are the OHT that reported the confection of it (6,7). In addition, evaluating data from the second cycle of PMAQ-AB, Cunha et al showed that the distribution of teams that performed dental prostheses across the country was unequal and, the provision was almost restricted to partial and total removable prostheses (8).…”
Section: Introductionmentioning
confidence: 99%
“…The PMAQ-AB is organized in four phases (adherence and contractualization, development, external evaluation, and recontratualization), forming continuous cycles of evaluation, which seek to overcome some challenges for PHC qualification, such as the precariousness of the physical structure and the unsatisfactory conditions of Basic Health Units. 3 Evaluations using data from the 1st and 2nd cycle of PMAQ-AB have already addressed the work process of the teams, 4 user satisfaction with services rendered, 5 service provisions and basic care procedures, 6,7 and availability of instruments in OHS. 8 The provision of effective healthcare services is directly influenced by infrastructure conditions, and availability and adequacy of equipment, as well as materials and supplies that meet the needs of the service.…”
Section: Introductionmentioning
confidence: 99%